Evaluation of semen parameters of Brahman graded bull compared to Holstein graded and Local bulls using Computer Assisted Sperm Analyzer - Islam, Md. Rafikul; Husain, Syed Sakhawat; Talukder, Md. Kutub Uddin; Rahman, Md. Shafiqur (Journal of the Bangladesh Agricultural University, 2020)
An experiment was conducted to characterize, compare, estimate of heritability, and genetic and phenotypic correlations of semen parameters of three genetic groups of bulls. The study was carried out at the Central Cattle Breeding and Dairy Farm, Saver, Dhaka from April to November, 2015. A total of 16 bulls from three genetic groups namely Brahman graded (8), Friesian graded (5) and Local (3) bulls were selected. Motility % and sperm concentration (×106/ml) were observed using Computer Assisted Sperm Analyzer (CASA). Data were analyzed using SAS Computer Package Program, version 9.1.3. Analysis of data showed that, individual genotypes had significant (p<0.05) effect on semen parameters. The maximum sperm concentration (×106/ml) was found as 1516.59±33.07 for Local group (LG), intermediate as 1380.38±19.06 for Brahman groups (BG) and lowest as 1105.03±22.54 in Friesian group (FG), respectively. The season had also significant (p<0.05) effect on semen parameters. The estimated heritability for the semen production traits were medium to high as 0.39 to 0.51, 0.36 to 0.48 and 0.35 to 0.44 for BG, FG and LG, respectively. The strongest positive genetic and phenotypic correlations were noticed between the related semen parameters for all the genetic groups. Through ranking of different traits used in this study for each genotypes it is signified that Brahman genotypes stood 1st position in terms of selection index value which has newly been introduced for beef production in Bangladesh. J Bangladesh Agril Univ 18(2): 442–448, 2020 https://doi.org/10.5455/JBAU.81689